Assessment of technician barcode scanning verification compared to pharmacist verification. (25th January 2019) - Shelton, Annie U; Wolf, Matt; Franz, Noah; Brummond, Philip W
Abstract: Purpose: This study aims to show the feasibility and sustainability of technician barcode scanning verification as an alternative to pharmacist visual verification of first dose medications in an acute care setting. Methods: A two-phase, noninferiority, single-center study was conducted to compare the accuracy of technician barcode scanning verification to pharmacist visual verification of pre-packaged first dose medications within a large acute care medical center. In phase 1, a pharmacy technician utilized barcode scanning as a means of verification. These preparations were then re-verified for accuracy by pharmacist visual verification. In phase 2, the verification order was reversed, starting with pharmacist visual verification of first doses, which were subsequently re-verified by a technician utilizing barcode scanning. Accuracy and efficiency (first dose processing time) of each phase was analyzed via error logs and retrospective dose tracking. Results: A total of 12, 328 first dose preparations were included in the analysis and showed no difference between technician barcode scanning verification and pharmacist visual verification. Retrospective time study showed a 4-minute decrease in processing time when doses were verified by technician barcode scanning. Based on initial study outcomes, a variance was granted to pilot first dose tech-check-tech by the Wisconsin State Board of Pharmacy. Conclusion: This study determined that there is no difference in verification accuracy between technician barcode scanning verification and pharmacist visual verification of first doses in an acute care setting. Through leveraging technology and skill mix, Froedtert Hospital was able to provide the same level of patient safety while decreasing pharmacy processing time, developing our technician workforce, and reallocating pharmacist staff from distributive roles in central pharmacy to decentralized clinical activities.